Analisis Efisiensi Teknis pada Usaha Peternakan Sapi Perah Rakyat di Kecamatan Lembang (Technical Efficiency Analysis of Smallholder Dairy Farming at Lembang) - Anggraeni Efrika Cahyawati; Bagus Priyo Purwanto; Suryahadi Suryahadi (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2014)
This study aims to analyze the level of techincal production efficiency of smallholder dairy farming at Lembang, West Java Province. Data were collected from selected 60 farmers by using proportionate stratified judgemental sampling method. The respondents were categorized into two groups based on lactating cow : category 1 = 1-5 lactating cows, and category 2 = 6-10 lactating cows. Each category comprised of 30 respondents. The data analysis in this study used stochastic frontier production. The result of the analysis of category 2 indicated that the presence of technical inefficiency had effects in milk production by the significant estimated gamma coefficient, the likelihood ratio test and the predicted technical within farmers. The estimated gamma parameter (ɣ) of model for production function was 0.99, indicating about 99 percent of variation in output milk among farmers was due to differences in their technical efficiencies. The result indicated that smallholder dairy farming in Lembang is efficient with an average of technical efficiency of 91 percent. Factors influencing production efficiency are farmer's age, farming experience, and livestock ownership.Keywords : dairy farms, technical efficiency, stochastic frontier analysis